If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 3(2x + -4) = -9 + -4x Reorder the terms: -7x + 3(-4 + 2x) = -9 + -4x -7x + (-4 * 3 + 2x * 3) = -9 + -4x -7x + (-12 + 6x) = -9 + -4x Reorder the terms: -12 + -7x + 6x = -9 + -4x Combine like terms: -7x + 6x = -1x -12 + -1x = -9 + -4x Solving -12 + -1x = -9 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -12 + -1x + 4x = -9 + -4x + 4x Combine like terms: -1x + 4x = 3x -12 + 3x = -9 + -4x + 4x Combine like terms: -4x + 4x = 0 -12 + 3x = -9 + 0 -12 + 3x = -9 Add '12' to each side of the equation. -12 + 12 + 3x = -9 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = -9 + 12 3x = -9 + 12 Combine like terms: -9 + 12 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 30-13y+y^2=0 | | 9n-7=5n-19 | | y^2-3y=-2 | | 1/7^2x=1/49 | | 4p=-14 | | -210+16z+2z^2=0 | | h=-16t^2+19.5t+6.5 | | -2.4y=9.6 | | 2z^2+16-210=0 | | 7x+3=2x-66 | | 6x-(5x+-1)=2 | | 0.4y=-0.8 | | y=(-2/3)x-5 | | 35(2x-1)=(x+4)+3x | | 3x-9=4+3(2x-1) | | 13(x-52)=26 | | 5y-8=15-6Y | | x+5+4x-2+3x-1=66 | | 2z/3.6 | | 75-3x=8x+2 | | (4x+8)/(x-3) | | 6x+7=107+4x | | y=dx+c | | 2+w/6=12/19 | | 3/5+2/9 | | 6x-4=4x-100 | | -144+100z^2=0 | | -1/6k+5/4=-3+4/3k | | 100.041/8 | | 7(x+3)-6=24-3x-9+10x | | 100z^2-144=0 | | (4x+8)/(x-3)=0 |